2022
DOI: 10.1002/fsn3.2684
|View full text |Cite
|
Sign up to set email alerts
|

Does propolis have any effect on rheumatoid arthritis? A review study

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease in which inflammation and oxidative stress play a key role in its pathophysiology. Complementary therapies along with medications may be effective in the control of RA. Propolis is a natural substance extracted from beehives, which have confirmed anti‐inflammatory and antioxidant effects. The present study aimed to review the possible effects of propolis on inflammation, oxidative stress, and lipid profile in patients with RA. English articles in online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 227 publications
0
24
0
Order By: Relevance
“…Identifying modifiable CVD risk factors is of great significance in terms of setting up primary prevention strategies. Unhealthy diet has been considered a key modifiable risk factor for many chronic diseases [4][5][6][7]. Lifestyle changes, especially modification in dietary pattern, are recommended as part of prevention and control strategies for metabolic disorders such as dyslipidemia and insulin resistance [8].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying modifiable CVD risk factors is of great significance in terms of setting up primary prevention strategies. Unhealthy diet has been considered a key modifiable risk factor for many chronic diseases [4][5][6][7]. Lifestyle changes, especially modification in dietary pattern, are recommended as part of prevention and control strategies for metabolic disorders such as dyslipidemia and insulin resistance [8].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory effects of propolis have been confirmed by numerous studies in the literature [ 70 , 71 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ]. Several studies have shown that propolis (as an aqueous or ethanol preparation) can act as a strong anti-inflammatory agent against acute and chronic inflammations [ 70 , 71 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ].…”
Section: Role Of Propolis and Its Components In Allergymentioning
confidence: 79%
“…The anti-inflammatory effects of propolis have been confirmed by numerous studies in the literature [ 70 , 71 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ]. Several studies have shown that propolis (as an aqueous or ethanol preparation) can act as a strong anti-inflammatory agent against acute and chronic inflammations [ 70 , 71 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ]. The efficacy of aqueous extract of propolis (WSDP) was confirmed in an acute model of inflammation (paw edema induced by PGE2) and a chronic model of inflammation (arthritis induced by formaldehyde) [ 130 ].…”
Section: Role Of Propolis and Its Components In Allergymentioning
confidence: 79%
See 1 more Smart Citation
“…RA affects approximatley 1% of the world's population and is more common in women than men (McInnes & Schett, 2017). Immune cells of T, B lymphocytes, and macrophages are involved in the pathophysiology of RA (Nattagh‐Eshtivani et al, 2022). These cells cause oxidative stress, systemic and localized inflammation through the overproduction of inflammatory cytokines (Cooles & Isaacs, 2011; Quiñonez‐Flores et al, 2016).…”
Section: Introductionmentioning
confidence: 99%